Viaje maldito en “La universidad desconocida”, de Roberto Bolaño - Gómez, Leila; Tuninetti, Ángel (Studia Romanica Posnaniensia, 2013)
This paper focuses on the seldom studied poetry of Roberto Bolaño, using "La Universidad Desconocida", the exhaustive compilation published posthumously in 2007. Although Bolaño received wide recognition and many awards for his novels, he defined himself as a poet. In his poetry, we find the same topics and tendencies that he developed in the characters and plots of his narratives. A prime example is "Los detectives salvajes", a novel about a group of young rebel poets in the Mexico of the seventies. Bolaño’s poet characters, as well as his travels, exiles and criticisms of the literary establishment, take on a new light when compared alongside his poetry. this article explores the modes of poetic production as understood by Bolaño, as a way of life outside universities, the literary canon, and any other institutional networks. Instead, his poetic production is marked by the figure of Arthur Rimbaud as the archetype of the cursed poet.